Dapur Sehat: Solusi Inovatif Mahasiswa Giat 9 untuk Mengatasi Stunting di Kelurahan Sidorejo Lor - Amidi Amidi; Nabila Meilani Dewi; Farah Dilla Marifatul Aaliyah (Jurnal Bina Desa, 2025)
Stunting remains a major challenge in Indonesia, particularly in rural areas like Sidorejo Lor. The "Dapur Sehat Atasi Stunting" (DASHAT) program was designed to address this issue through an educational and participatory approach focused on enhancing community understanding of balanced nutrition. The program's objective is to improve community knowledge and skills in creating nutritious menus utilizing easily accessible local foods. The target audience is the community of Sidorejo Lor, particularly Posyandu and PKK members. Methods used include counseling, training, cooking demonstrations, and 30-day mentoring. The implementation process began with education on basic nutrition, followed by training and cooking demonstrations to provide practical skills. Intensive mentoring was conducted to ensure the application of DASHAT menus in daily life. The results of this program indicate a significant increase in nutritional understanding and cooking skills, as well as active participation in program activities. The program successfully encouraged dietary changes in the community, potentially reducing stunting rates in Sidorejo Lor. This success highlights the importance of educational and participatory approaches in addressing public health issues.